2019
DOI: 10.1038/s41598-019-55499-8
|View full text |Cite
|
Sign up to set email alerts
|

Phytoseiid predatory mites can disperse entomopathogenic fungi to prey patches

Abstract: Recent studies have shown that predatory mites used as biocontrol agents can be loaded with entomopathogenic fungal conidia to increase infection rates in pest populations. Under laboratory conditions, we determined the capacity of two phytoseiid mites, Amblyseius swirskii and Neoseiulus cucumeris to deliver the entomopathogenic fungus Beauveria bassiana to their prey, Frankliniella occidentalis. Predatory mites were loaded with conidia and released on plants that had been previously infested with first instar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The potential for predators to protect their prey populations from the harmful effects of parasitism is intuitive and has promising conservation and public health implications (Packer et al 2003;Ostfeld & Holt 2004). In agricultural pest systems, management sometimes has the opposite goal: using predators to facilitate pathogen spread to better limit pest abundances (Roy et al 2001;Zhanget al 2015;Lin et al 2019). However, there is surprisingly mixed evidence for the effect of predators on parasitism in their prey, with roughly as many studies finding that predators increase disease as finding a decrease (Richards et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential for predators to protect their prey populations from the harmful effects of parasitism is intuitive and has promising conservation and public health implications (Packer et al 2003;Ostfeld & Holt 2004). In agricultural pest systems, management sometimes has the opposite goal: using predators to facilitate pathogen spread to better limit pest abundances (Roy et al 2001;Zhanget al 2015;Lin et al 2019). However, there is surprisingly mixed evidence for the effect of predators on parasitism in their prey, with roughly as many studies finding that predators increase disease as finding a decrease (Richards et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…If predators increase parasitism but fail to have persistent effects on prey population densities or prey fitness, the predator-spreader interaction would be of limited use for understanding prey population dynamics. Studies on agricultural arthropod pests which manipulate both predators and parasites typically focus on prey density as the key outcome of interest (Kaneko 2006;Vance-Chalcraft et al 2007;Agboton et al 2013;Linet al 2019); these studies often focus on whether predator and parasite effects on pest species are additive, substitutive, antagonistic, or synergistic in order to best accomplish biological control of pest species (Roy et al 2001;Zhang et al2015;Lin et al 2019). Measuring effects on population density does generally require longer-term studies than those simply reporting parasite outcomes, but the amount of additional time required varies substantially with prey life history.…”
Section: Beyond Single Mechanism Studiesmentioning
confidence: 99%
“…In addition, organic fertilizers could serve as a growth substrate for EPF mycelium (Klingen et al 2002;Noble et al 2018). Organic fertilizers also increase the abundance of soil-dwelling arthropods that are potential hosts for EPF or that act as vectors in spreading and transmitting EPF spores (Ali-Shtayeh et al 2002;Thiele-Bruhn et al 2012;Anslan et al 2018;Lin et al 2019). It has been suggested that some EPF are more sensitive to exogenous disturbances than others.…”
Section: Discussionmentioning
confidence: 99%
“…A method has been developed in which the soil predatory mite Stratiolaelaps scimitus and the plant-inhabiting mites N. cucumeris and A. swirskii collect and transport B. bassiana conidia directly from a commercial rearing substrate to control the western flower thrips, F. occidentalis [ 44 ]. A study by Lin et al [ 54 ] confirmed that loading A. swirskii and N. cucumeris with B. bassiana can increase their capacity to suppress thrips populations by combining predation and the dispersal of pathogens. Wu et al [ 55 ] demonstrated that another phytoseiid mite, Neoseiulus barkeri Hughes (Acari: Phytoseiidae), is able to disseminate B. bassiana conidia.…”
Section: Discussionmentioning
confidence: 99%